Design and Operation of an Irradiance Measurement Network. (May 2015) - Schenk, H.; Hirsch, T.; Wittmann, M.; Wilbert, S.; Keller, L.; Prahl, C.
Abstract: The area covered by large-scale solar thermal power plants extends out to one up to several square kilometers. During the passage of clouds, the solar fields of these plants get partially shaded while other areas remain irradiated. In the case of line-focus plants these transient effects lead to inhomogeneous outlet temperatures of collector loops, while in point-focus plants the flux density at the receiver is influenced. Nowadays, yield prognoses based on measured irradiation data at one specific site, neglecting the effect of inhomogeneous irradiation. One of the aims of the Turikon project is to provide temporally and spatially resolved maps of direct normal irradiance (DNI). On this account, a distributed irradiance measurement network has been installed at the Plataforma Solar in Spain within the research activities of the Turikon project. The network, which consists of 20 silicon pyranometers and a data acquisition system, is in operation since 2013, delivering distributed values for the global horizontal irradiation with a temporal resolution of one Hertz.In the present work a methodology is presented, that makes use of measurements from the network and additionally a vector of cloud movement, derived from shadow pictures. In that manner, data points can be shifted in the direction of cloud movement in order to obtain a temporally resolved DNI map that overlaps the circumference of the measurement network. In this publication, an example is presented that already shows the good applicability of the methodology. Subsequently, the methodology will be tested and validated with a broader data-base.